Legal redress for identity theft in Malaysia : hope or hype? - Zulhuda, Sonny (UiTM Melaka, Malaysia, 2012)
Identity theft is described as unlawful acquisitions of personal data that belongs to other individuals. It provides ammunition for further action such as credit cards forgery or impersonated bank accounts that are used as a platform for further crimes. Though identity theft incidents increase from time to time, they hardly end up in prosecution. This situation has been largely credited to the absence of the specific law on identity theft. Against this background, the enactment of Personal Data Protection Act 2010 triggers huge interests. The law, which seeks to regulate the processing, storing and use of personal data of individuals in commercial activities, is now expected to fill the gap on identity theft issues. This paper analyzes to what extent this hope can be realised, by assessing the relevant provisions in the Act.